I hope this is the correct form of the equation that you are trying to write:
![(4)/(3x) +(5)/(4) =(3)/(x)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/a12dx9ws39gq221drv6qn0yr34k9m4pcyl.png)
First step to solve this equation, multiply each sides with the common denominator 12x so that we can get rid of fraction form. So,
![(4)/(3x)*(12x) +(5)/(4)*(12x) =(3)/(x)*(12x)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/vzkbnhh3bnjhhw5k3r9kusb70vgdtecder.png)
Next step is to cancel out the common factor from both numerator and denominator of each fractions.
4(4) + 5(3x) = 3(12)
16 + 15x = 36
16 + 15x - 16 = 36 - 16 Subtract 16 from each sides.
15x = 20
Divide each sides by 15 to isolate x.
![x = (4)/(3)](https://img.qammunity.org/2019/formulas/mathematics/middle-school/hkpamech2j2zh5rv5o1rw9i3upzcdsgvjh.png)
So, x = \frac{4}{3}
"Hope this helps!!"